2006
DOI: 10.1007/bf02715911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of twin-screw extrusion parameters on mechanical hardness of direct-expanded extrudates

Abstract: Mechanical properties of cereal (starch-based) extrudates are perceived by the final consumer as criteria of quality. We investigate one of the important characteristics of extrudates, mechanical hardness, which is one of the main texture parameters. Texture quality has an influence on taste sensory evaluation, and thus on the acceptability of the product. Characteristics that have great influence on acceptability are crispness, elasticity, hardness and softness. These attributes are narrowly related to, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Products extruded at a higher moisture content had greater hardness and lower fracturability. Brnčić et al (2006) also showed that the moisture content had the greatest impact on the texture of extrudates.…”
Section: Resultsmentioning
confidence: 92%
“…Products extruded at a higher moisture content had greater hardness and lower fracturability. Brnčić et al (2006) also showed that the moisture content had the greatest impact on the texture of extrudates.…”
Section: Resultsmentioning
confidence: 92%
“…The main effect of the addition of whey proteins is that they reduce WAI and increase WSI (Onwulata et al 2001;Kovaček et al 2003). The degree of shear is adjustable, but it is not possible to change screw configuration during the production to s 2 variance, R 2 correlation coefficient, R 2 adj adjusted correlation coefficient increase shear; likewise, it is not possible to change water flow during the production (Brnčić et al 2006). WSI is the function of used starch, in this case corn flour.…”
Section: Resultsmentioning
confidence: 98%
“…Consequently, it is also tied with the initial texture and change of the texture during chewing (Brnčić et al . ; Makri ). Texture is a set of parameters of quality that are closely related to the structural and mechanical properties of foodstuffs (Burubai et al .…”
Section: Introductionmentioning
confidence: 99%